2022
DOI: 10.1021/acsomega.2c02620
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Controlled Injection Method Using Support Templates for the Production of Chemobrionic Materials

Abstract: Chemobrionics is a research field about the well-known self-organized inorganic structures. Numerous research works have focused on controlling their growth pattern and characteristic features. In the present study, a controlled injection method is proposed to produce more regular self-assembled chemobrionics compared to the standard direct injection technique. This method involves the injection of a metal salt solution into an agarose support template filled with an anionic solution. The obtained structures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The observed crystals on the internal surface predominantly indicated the presence of magnesium silicate and NaCl salt, which was consistent with the results from EDS analysis ( Figure S1b,d ) and previous reports. 4 , 18 , 19 In contrast, the primary component found on the external smooth surface of solids formed in seed and injection experiments was magnesium oxide, while the relative quantities of magnesium silicate and sodium silicate were lower on these surfaces compared to those observed on the internal surfaces ( Figure S1a,c ). In the membrane experiment, it was observed that the surface morphologies were clearly different for the two sides of the precipitate: rough on the solution side ( Figure 3 e) and smooth on the side adjacent to the cellulose membrane ( Figure 3 f).…”
Section: Resultsmentioning
confidence: 95%
“…The observed crystals on the internal surface predominantly indicated the presence of magnesium silicate and NaCl salt, which was consistent with the results from EDS analysis ( Figure S1b,d ) and previous reports. 4 , 18 , 19 In contrast, the primary component found on the external smooth surface of solids formed in seed and injection experiments was magnesium oxide, while the relative quantities of magnesium silicate and sodium silicate were lower on these surfaces compared to those observed on the internal surfaces ( Figure S1a,c ). In the membrane experiment, it was observed that the surface morphologies were clearly different for the two sides of the precipitate: rough on the solution side ( Figure 3 e) and smooth on the side adjacent to the cellulose membrane ( Figure 3 f).…”
Section: Resultsmentioning
confidence: 95%
“…CB and BS incorporated BCB scaffolds were produced with the controlled injection method 27 . The system consisted of a New Era-100 syringe pump (USA) and a capillary tube to feed solutions, and a polypropylene centrifuge tube containing a hollow agarose template, which was 3.0 cm in height and had an internal space with a 3.0 mm diameter.…”
Section: Production Of Cb and Bs Incorporated Bcb Scaffoldsmentioning
confidence: 99%
“…These studies focused on various physicochemical factors [6][7][8][9][10][11][12][13][14][15] including oscillatory growth of hollow microtubes, 12 tube growth with a pinned bubble, 14 and spiral growth of the tube controlled by the application of magnetic force. 15 Recently, chemical gardens have received attention as biomimetic materials due to their ability to form a variety of self-assembled structures, [16][17][18][19][20][21][22][23][24][25][26][27] such as silica-rich biomimetic mineral 20 and self-assembled nanostructures. [21][22][23][24][25][26][27] These diverse approaches to chemical gardens and their self-organized structures in physics, chemistry, and biology, nucleated a new research area called "chemobrionics".…”
Section: Introductionmentioning
confidence: 99%
“…15 Recently, chemical gardens have received attention as biomimetic materials due to their ability to form a variety of self-assembled structures, [16][17][18][19][20][21][22][23][24][25][26][27] such as silica-rich biomimetic mineral 20 and self-assembled nanostructures. [21][22][23][24][25][26][27] These diverse approaches to chemical gardens and their self-organized structures in physics, chemistry, and biology, nucleated a new research area called "chemobrionics". 1,[21][22][23][24][25][26] In addition, the morphology and composition of the chemical gardens under the different conditions have been studied by various analytical methods and techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation